(untitled) (The Journal of Medicine, Humanity and Media, 2025)
Patients’ self-narratives articulate the social and psychological experiences of disease. Listening to these narratives enhances understanding of their pain and distress, aiding in rediscovering life’s meaning post-illness. Using grounded theory analysis, this study developed an "element-identity-strategy" model from Zhihu cancer narratives, highlighting elements like narrative closure, feedback, and local culture. Patients use dimensions of body, self, and relationships in their narratives to create identities such as physical sufferers and self-worth victims. Cancer survivors draw from personal and cultural experiences to reestablish value through role reconstruction. Lacking emotional and social support, they turn to familial ties and integrate new social supports through online and offline interactions, gaining strength to rewrite their life’s narrative.